The Regeneration of Urban Blue Spaces: A Public Health Intervention? Reviewing the Evidence - Brückner, Anna; Falkenberg, Timo; Heinzel, Christine; Kistemann, Thomas (Frontiers in Public Health, 2022)
Research in recent years has demonstrated that urban surface waters (“urban blue spaces”) can provide beneficial effects on human health and wellbeing. Despite blue spaces prevailing on urban development agendas across the world, little investigation has been done whether and how the regeneration of such spaces is used as a (community-based) public health intervention. Therefore, a review was conducted to analyze urban blue space regeneration projects in terms of their significance for public health. Results show that the regeneration of urban blue spaces displays a diversity of intervention types and that it follows certain development trends seen in general urban regeneration: Similarities mainly arise in relation to objectives (multi-dimensional goals with increasing focus on environmental sustainability and economic interests), stakeholders (shift to multi-actor governance with a rise of partnerships and community participation), and funding (prevalence of mixed financial schemes and increasing reliance on external funding sources). Although threefold public health effects have been noted across the projects (i. behavioral changes towards healthier lifestyles, ii. healthier urban environments, iii. health policy changes), results of this review indicate that the potential to use urban blue regeneration as a community-based health intervention has yet to be realized.